Tanggung Jawab Direksi Persero Pada Pengadaan Barang dan Jasa di BUMN dalam Hal Terjadi Kerugian - Rika Maryam (LPPM Universitas Harapan Bangsa, 2023)
In the current era of transparency of the procurement of goods and services in the State Owned Enterprises (BUMN), a lot of scrutiny of the public because it is considered unprofessional, inefficient and not transparent so that adds to costs incurred by the state / government to maintain its existence. Public assessment of the performance of directors, raises the question of what exactly is at the root problems that lead to inefficient and not optimal performance of directors in the management of BUMN. How the position, role and legal responsibility of directors in the procurement of goods and services in the state? How the application of the principle of standard operational procedure in the process of procurement of goods and services in state-owned enterprises so as to create good corporate governance. Based on the research results it can be known that there was no strict regulation in the Law on BUMN regarding the position and role of directors in losses in the process of procurement of goods and services by state enterprises. In the law only outlines the duties and liabilities of directors which will give rise to legal liability not only in terms of the civil law but also in terms of criminal law if it is proved that the directors do perversity of its legal obligations in performing the management of the company's adverse BUMN. But directors also can defend against him through the principles of the business judgment rule if it can prove that in the process of procurement of goods and services sesusai with standard operation procedures, and implemented in good faith and honest so that losses in the company was not caused due to errors or omissions arising directors of the self itself.